EPS dan DER: Prediktor ROA di Sub Sektor Plantation & Crops - Siagian, Valentine (EKALAYA : Jurnal Ekonomi Akuntansi, 2023)
This study aims to analyze the effect of Earnings Per Share (EPS) and Debt-to-Equity Ratio (DER) on Return on Assets (ROA) in the plantation and plantation subsectors in 2019-2022. The samples used in this study were plantation and crops sub-sector companies listed on the Indonesia Stock Exchange (IDX). The data analysis method used is  multiple regression  The results showed that EPS had a positive effect on ROA while DER had a negativ eeffect in the plantation and plantation subsectors. In addition, this study also shows that EPS has a greater influence on ROA than DER. This finding can be explained by the fact that EPS is an important measure of financial performance for investors, while DER tends to be used by companies to manage financial risks. This research makes an important contribution to plantation and crop subsector stakeholders in making investment decisions. The practical implication of this research is that plantation and plantation subsector companies should focus on improving their financial performance by increasing EPS and managing DER wisely to increase ROA.